AB1125 LESS SEVERE SYNOVITIS IN PATIENTS WITH KNEE OSTEOARTHRITIS IS ASSOCIATED WITH HIGHER SELF-REPORTED PAIN INTENSITY 12 MONTHS AFTER TOTAL KNEE ARTHROPLASTY – AN EXPLORATORY COHORT STUDY. (June 2019) - Petersen, Kristian Kjær; Arent-Nielsen, Lars; Boesen, Mikael; Vela, Jonathan; Skou, Soeren; Eld, Mikkel; Al-Mashkur, Nasir Musa; Riis, Robert; Simonsen, Ole
Abstract : Background: Synovitis is a pain generator in patients with osteoarthritis and associated with upregulation of pro-inflammatory cytokines, which have been found to lead to pain sensitivity and worse self-reported pain(1). Objectives: This study aimed to investigate the association between pre- and perioperative synovitis from imaging and histology and self-reported pain 12 months after total knee arthroplasty (TKA). Methods: Preoperative synovitis was assessed from MRI data of the knee by 11 point synovitis score a.m Guermazi (2) using contrast enhanced MRI (CE-synovitis) and heuristic time intensity curve analysis of the dynamic contrast enhanced MRI (DCE-MRI) data using the DYNAMIKA® software (Image Analysis group, London) providing Dynamic Enhanced MR Quantification (DEMRIQ) Indices (3). Perioperative synovitis was also assessed from biopsies of the synovium in 6 predefined places graded histologically a.m Krenn (4). Worst pain within the last 24-hours (visual analog scale, VAS, 0-100) was assessed before and 12 months after TKA. Patients were divided into a low-pain (VAS≤30) and a high-pain (VAS>30) group based on 12-months postoperative VAS. Results: Twenty-six patients had full pre- and postoperative data and were analysed. The high-pain group had significantly lower CE-synovitis (P=0.03), DCE-MRI inflammation indices (DEMRIQ-inflammation) (P<0.03) and a trend towards lower histologically assessed synovitis grades (P=0.077) compared to the low-pain group at baseline. Preoperative synovitis scores were also inversely correlated with pain 12-months after TKA, CE-synovitis (R = - 0.455, P = 0.022) and DCE-MRI inflammation (R = -0.528, P = 0.007), indicating that more severe preoperative synovitis is associated with less severe pain at 12-months. Conclusion: Higher preoperative synovitis scores are associated with less postoperative pain 12-months after TKA. Further, correlation analysis revealed that less severe preoperative synovitis was associated with worse pain 12-months after TKA, suggesting that CE and DCE-MRI synovitis quantification could be used as imaging markers for prediction of good surgical outcomes. References: [1] Schaible HG. Nociceptive neurons detect cytokines in arthritis. Arthritis Res. Ther. 2014:470. [2] Guermazi A, et al. Assessment of synovitis with contrast-enhanced MRI using a whole-joint semiquantitative scoring system in people with, or at high risk of, knee osteoarthritisAnn. Rheum. Dis. 2011 [3] Riis RGC, et al. The association between histological, macroscopic and magnetic resonance imaging assessed synovitis in end-stage knee osteoarthritis Osteoarthr. Cartil. 2017; [4] Krenn V, et al. Grading of chronic synovitis-a histopathological grading system for molecular and diagnostic pathology. Pathol. Res. Pract. 2002 Acknowledgement: Image Analysis Group, for providing DYNAMIKA software and support for the DCE-MRI/DEMRIQ analysis Disclosure of Interests: Kristian Kjær Petersen: None declared, Lars Arent-Nielsen: None declared, Mikael Boesen Shareholder of: Image Analysis Group, UK, Grant/research support from: Image Analysis Group, UK, OAK Foundation, EUROSTAR, Consultant for: Esaote, Eli Lilly, Celgene, Carestream, UCB, Abbvie, Pfizer, Astra Zeneka, Roche, Siemens, Image Analysis Group, Jonathan Vela: None declared, Soeren Skou: None declared, Mikkel Eld: None declared, Nasir Musa Al-Mashkur: None declared, Robert Riis Consultant for: Image analysis Group, Ole Simonsen: None declared